PERAN GURU IPS UNTUK MENUMBUHKAN LITERASI SOSIAL SISWA KELAS VIII DI SMPN 3 SOLOK SELATAN - Mira Sari; Wibi Wijaya; Waza Karia Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of social literacy as a student's ability to interact, collaborate, participate, and act responsibly within society. Strengthening social literacy is a key objective of Social Studies instruction, as students are expected not only to master knowledge but also to apply it in social life. This study aims to describe the role of Social Studies teachers in fostering social literacy among Grade VIII students at SMPN 3 Solok Selatan. Grounded in constructivist theory, social knowledge and skills are actively constructed by students through experience, interaction, and direct engagement within their learning environment.This study employs a qualitative approach with a descriptive research design. Research informants included the school principal, Social Studies teachers, guidance and counseling teachers, the Student Council president, and Grade VIII students. Data collection techniques involved observation, interviews, and document analysis. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research findings indicate that Social Studies teachers play a role in fostering student social literacy through three primary functions. As facilitators, teachers provide learning experiences that directly involve students in maintaining the cleanliness of the school environment, thereby cultivating social concern and responsibility. As motivators, teachers encourage students to actively engage in discussions, collaborate, and express their opinions, thereby enhancing student participation, communication skills, and self-confidence. As role models, teachers demonstrate mutual respect, cooperation, and conflict resolution through deliberation, helping students develop emotional management skills and the ability to build positive social relationships.